CUSTOMER NEEDS AS THE FACTOR OF INCREASING SERVICE QUALITY IN HOTEL BUSINESS - Sadikova Nargiza Maxsudovna (Лучшие интеллектуальные исследования, 2024)
The relationship between the concept of the quality of the hotel service and the needs of the client is examined, as well as the possibility of obtaining competitive advantages due to the correctly estimated expectations.